2020
DOI: 10.1101/2020.08.21.262063
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stable isotope informed genome-resolved metagenomics uncovers potential trophic interactions in rhizosphere soil

Abstract: The functioning, health, and productivity of soil is intimately tied to a complex network of interactions, particularly in plant root-associated rhizosphere soil. We conducted a stable isotope-informed, genome-resolved metagenomic study to trace carbon from Avena fatua grown in a 13CO2 atmosphere into soil. We collected paired rhizosphere and non-rhizosphere soil at six and nine weeks of plant growth and extracted DNA that was then separated by density using gradient centrifugation. Thirty-two fractions from … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 112 publications
0
18
0
Order By: Relevance
“…These results suggest that bacteria should be considered alongside eukaryotes and viruses as important predators in microbial food webs. Similarly, a recent metagenomic qSIP analysis using a 13 C-CO 2 tracer introduced via plant root exudates found that 13 C recovery in metagenomes associated with putative predator bacteria was comparable to the recovery in viruses and substantially higher than that in predatory eukaryotes (40). Slower growth might be expected if bacterial predators were inactive or dormant, as are many soil microorganisms (41).…”
Section: Resultsmentioning
confidence: 94%
“…These results suggest that bacteria should be considered alongside eukaryotes and viruses as important predators in microbial food webs. Similarly, a recent metagenomic qSIP analysis using a 13 C-CO 2 tracer introduced via plant root exudates found that 13 C recovery in metagenomes associated with putative predator bacteria was comparable to the recovery in viruses and substantially higher than that in predatory eukaryotes (40). Slower growth might be expected if bacterial predators were inactive or dormant, as are many soil microorganisms (41).…”
Section: Resultsmentioning
confidence: 94%
“…In this study, we investigated the cooccurrence patterns of bacterial and fungal communities over space and time, using amplicon sequences of bacterial 16S and fungal internal transcribed spacer (ITS) rRNA genes, in soil samples from a greenhouse experiment that has previously yielded information on bacterial succession and cooccurrence patterns (47,48) as well as potential trophic interactions revealed by stableisotope-informed genome-resolved metagenomics (49). This experiment used soil from a California annual grassland and the annual grass Avena fatua, which is common and naturalized to the area from which the soil was collected.…”
mentioning
confidence: 99%
“…These results suggest that bacteria should be considered alongside eukaryotes and viruses as important predators in microbial food webs. Similarly, a recent metagenomic qSIP analysis using a 13 C-CO 2 tracer introduced via plant root exudates found that 13 C recovery in metagenomes associated with putative predator bacteria was comparable to the recovery in viruses and substantially higher than predatory eukaryotes (53). Slower growth might be expected if bacterial predators were inactive or dormant, as are many soil microorganisms (54).…”
Section: Resultsmentioning
confidence: 94%